Web-based Geographic Information System Design of Rabies Spread in Bali - I. A. K. Sita Laksmita; A. A. Kompiang Oka Sudana; Putu Wira Buana (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
Rabies is still a serious threat in the province of Bali. Because of that Bali need a good management system service that can process data and information to support the government to make decision for preventing rabies outbreak. Nowadays, data management still uses spreadsheet technology that oriented to attribute data. Geographic Information System (GIS) is a system that has the ability to process, analysis the process and analyzes spatial data or data with geographic coordinates. This article will discuss the implementation of GIS that show the spread of rabies in the province of Bali by using GeoServer as the Open Geospatial Consortium (OGC) standards-compliant server to provide geospatial data via web services. These GIS application, supported by PostGIS database as storage and processing of spatial data and OpenLayers as an interface. This application can support government for making priority decision to focus on areas which has the most high of rabies outbreak.DOI: http://dx.doi.org/10.11591/ij-ict.v1i1.589